Screening of White-Rot Fungi as Biological Control Agents Against Ganoderma philippii - Afrida Sitompul; Aswardi Nasution (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2020)
Ganoderma philippii is the causal agent of root rot disease causing economic losses to Acacia plantations. In an effort to control the Ganoderma root-rot disease, we isolated and screened white-rot fungi as biological control agents. We collected 107 samples from forestry plantations in Riau Province. The fungi were isolated from rotten wood including trunks and twigs, and fruiting bodies. Out of the 107 samples, 28 from rotten woods and 51 from fruiting bodies were successfully isolated. Screening of the isolated fungi was done on wood block, wood disc, and wood-powder-containing agar. Eleven isolates showed fast growth on wood block and in subsequent second screening in dual culture on wood disc, three isolates showed fast growth and were capable of overgrowing G. philippii. The third screening was to examine quantitative growth rate of selected fungal isolates on malt extract agar wood powder (MEA-WP) two isolates were selected. These two isolates have shown potential as biological control agents of the root-rot pathogen, G. philippii.